A procedure for matching the near-fault ground motions based on spectral accelerations and instantaneous power. Issue 4 (November 2021) - Zengin, Esra; Abrahamson, Norman A
Selection of ground motions for use in nonlinear dynamic analysis is one of the most critical steps for both code-based design and probabilistic seismic risk assessment of structures. In practice, time-domain spectrum-matching methods, which add wavelet functions to an initial acceleration time series, have been widely used to obtain a record whose response spectrum closely matches the desired target spectrum. Although the spectral shape is known to be a good predictor of structural response, it does not represent the critical aspects of the velocity pulses, such as pulse amplitude and pulse period for near-fault ground motions. The Instantaneous Power ( IP ( T 1 )), defined as the maximum rate of change of energy of the bandpass-filtered velocity time series over a short time interval given by half of the structural period, has been shown to be an effective alternative parameter to capture effects of the presence of a velocity pulse and the pulse period in near-fault record selection. We introduce an approach to modify time series so as to simultaneously match a target response spectrum and IP spectrum over a specified period interval. We demonstrate that the records modified using the proposed approach produce results comparable to those obtained using unscaled records, and prevent potential bias in structural response, relative to results when matching is performed without consideration of IP .